The presence of stearamide as a rubber chemical in silica loaded-styrene butadiene rubber: The curing properties. Issue 1 (December 2020) - Dhoni, R; Ginting, M; Surya, I
Abstract: This research-study investigated the influences of stearamide on the curing properties of silica-loaded styrene-butadiene rubber (SBR). The SBR was loaded with silica at a fixed loading (thirty phr) and the stearamide was added into the silica-loaded SBR compounds with varied doses from two to eight phr. The influences of stearamide additions on the scorch time, optimum curing time and cure rate index (CRI) of silica-loaded SBR were investigated. It was observed that the stearamide caused an enhancement in the rate of the curing process on the SBR compounds. The stearamide decreased both the times to scorch and optimum curing times but increased the CRI. The bigger the stearamide doses caused in the lower were the scorch time, curing time and CRI. The decreases in CRI was attributed to the role of a reactant that interacted chemically inside the silica-loaded SBR compounds. The amine content of stearamide presumably triggered the chemical reaction between the SBR, silica filler and amine itself.